EVALUATION OF HAZARDOUS WASTE MANAGEMENT OF THE MANUFACTURING INDUSTRY IN PT. X - rohan, Prayudha; Kancitra Pharmawati (Department of Environmental Engineering (Prodi Teknik Lingkungan), Fakultas Sains dan Teknologi, UIN Ar-Raniry Banda Aceh, 2024)
PT. X is the largest viscose fibre manufacturing company in Indonesia. Production at PT X generates hazardous and toxic waste, potentially harming human health and the environment. The hazardous waste generated is oil, electronic waste, used batteries, tubular lamps, asbestos and rock wool, and hazardous packaging with the most significant quantity of WWTP (Wastewater Treatment Plant ) sludge and cellulose alkali. Exposure to high concentrations of cellulose alkali can cause acute poisoning and even death. This study aims to evaluate the management of hazardous waste by considering the Minister of Environment and Forestry Regulation No. 6 of 2021, the Minister of Environment and Forestry Regulation No. 14 of 2013 on symbols and labels of hazardous and toxic waste, and Government Regulation No. 22 of 2021 on the implementation of environmental protection and management, then the level of conformity is assessed using the Likert method. There are several aspects of hazardous and toxic waste management, namely aspects of reduction, packaging, collection, symbol and labelling, and temporary storage. The results of the suitability of hazardous waste management from the aspects of reduction are 100%, packaging is 88%, collection is 100%, giving symbols and labels is 71%, and storage is 96%; from the average overall result, a value of 91% is obtained and categorised as ‘very good’.